Research on the formation logic, practical problems and improvement path of data intellectual property registration system - ZHENG Shiyi (大数据, 2025)
In the era of the digital economy, data serving as a key factor of production, faces challenges in ownership confirmation and circulation. Although China has piloted data intellectual property registration systems in multiple regions, practical implementation reveals issues such as low legislative hierarchy, rough review mechanisms, and fragmented standard systems. Based on temporal, theoretical, and institutional logics, this paper analyzes the necessity of establishing a data intellectual property registration system, arguing that it aligns with the characteristics of data such as non-depletability and publicness, and draws on the logic of intellectual property protection. Drawing on practices from 17 pilot regions, the paper identifies key problems in the current system, including insufficient legal authority, unclear institutional roles, and deficiencies in formal examination. It then proposes improvement pathways in three areas: standard unification, rights balancing, and resource optimization.